The Ethics of Self-Disclosure on Social Media from the Perspective of Imam Al-Ghazali: An Analysis of the Concept of Digital Riya Among Z Generation - Muhammad Idil Fitri; Ramsiah Tasruddin (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
The development of social media has transformed how Z Generation constructs identity and engages in self-disclosure within digital spaces. This activity is not only related to communication needs but is also influenced by a culture of social validation through likes, comments, and followers. In certain contexts, self-disclosure may shift into performative behavior closely related to the concept of riy?’ in Islamic ethics. This study aims to analyze the phenomenon of Z Generation’s self-disclosure on social media through the moral perspective of Imam Al-Ghazali, particularly the concept of riy?’ as behavior oriented toward seeking human praise. This research employs a qualitative method using a library research approach. Data were collected from Imam Al-Ghazali’s works, especially Ihya’ ‘Ulum al-Din, as well as various academic literatures on social media and Z Generation digital culture. The findings reveal that social media has created a culture of digital validation that encourages individuals to construct performative identities in public spaces. Practices such as oversharing, flexing, and religious self-imaging may be understood as forms of digital riy?’ when their orientation shifts from self-expression to seeking social recognition. From Al-Ghazali’s perspective, the central issue lies in the motives and inner orientation behind such behavior. This study concludes that Al-Ghazali’s concepts of riy?’, sincerity, self-reflection, and self-control remain relevant as ethical foundations for social media use in the modern digital era.